Solar ultra-violet radiation and vitamin D synthesis in man - Webb, A.R. (1986)
The solar UVB radiation incident on a horizontal surface was measured and related to more routinely recorded meteorological variabIes in a study of the UVB climatology of the English East Midlands. Exposure of individuals in this climate was monitored and related to vitamin D status.